Insight Into the Strengthening Mechanism of the Al-Induced Cross-Linked Calcium Aluminosilicate Hydrate Gel: A Molecular Dynamics Study - Zhang, Gaozhan; Li, Yang; Yang, Jun; Ding, Qingjun; Sun, Daosheng (Frontiers in Materials, 2021)
Understanding and controlling of the mechanical properties of calcium aluminosilicate hydrate (C-A-S-H) gel is essential to the performance improvement of cementing materials. Employing the reactive molecular dynamics simulation, this study characterizes the mechanical properties and failure mechanism of cross-linked C-A-S-H that have Al/Si ratios ranging from 0 to 0.20. In these constructed C-A-S-H models, the Al-induced cross-linking effect on the aluminosilicate chains is well reproduced. With the incorporation of aluminate species, layered C-S-H structure gradually transforms into three-dimensional C-A-S-H. The uniaxial tensile tests show that Al-induced cross-links significantly increase the cohesive force and stiffness of C-A-S-H along both y and z directions. In C-A-S-H model with the Al/Si ratio equal to 0.2, in which all the bridging sites are cross-linked, the toughness along y direction significantly improves and the interlayer mechanical properties compare well with those within the layers. The deformation mechanism of the C-A-S-H structure is also studied. Results show that the de-polymerization of calcium aluminosilicate skeleton is the main route to uptake the loading energy. Both the increase of y and z directional strength of the structure can be related to the increasing polymerization of aluminosilicate chains along that direction. This demonstrates the important role of aluminosilicate chains in resisting the external tensile loading. Besides, during the failure process in C-A-S-H elongation, the hydrolysis reactions of calcium silicate skeleton are caused by the coupling effect of loading and interlayer water “attack”. While the Al-O-Si bond breakage results from the protonation of bridging oxygen atom, the hydrolytic reaction of Si-O-Si is initiated by five-coordinate silicon formation. Both pathways weaken the bridging bond and thus result in the breakage of T-O-Si, where T is Al or Si.